SOCIAL-EMOTIONAL COMPETENCE DEVELOPMENT IN YOUNG ADULTS: A THEORETICAL REVIEW - Sebastian VAIDA (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia, 2016)
One method to define a concept is to extract its definitions from multiple studies and models. In the present study, we used this qualitative approach to define the concept of social-emotional development in young adults, with all its facets. Based on specific keywords, we found over 400 articles concerning these concepts and, with specific criteria, narrowed it down to 30 studies. We then found very specific definitions for social-emotional competences, social competences and emotional ones. In the end, we found important similarities and differences between two intertwined concepts, emotional intelligence and social-emotional competence, with a wide range of applications.